LEADERSHIP STYLE OF FEMALE SCHOOL PRINCIPALS IN IMPROVING TEACHER PERFORMANCE AT SMP NEGERI 5 SIRENJA, DONGGALA REGENCY - Andinni Ma'rifah; Naima; Darmawansyah (Musawa: Journal for Gender Studies, 2025)
This study discusses the " female school principal's leadership style in improving teacher performance at SMP Negeri 5 Sirenja, Donggala Regency". The research uses a qualitative approach with a descriptive method. Data collection techniques include observation, interviews, and documentation. The obtained data are analyzed through data reduction, data presentation, data verification, and drawing conclusions. To check data validity, various types of triangulation and member checks are used.The results regarding the leadership style of the female school principal in improving teacher performance at SMP Negeri 5 Sirenja show that the female principal applies a transformational leadership style reflected in four main dimensions: (1) Idealized Influence (Charismatic), (2) Inspirational Motivation (Participative), (3) Intellectual Stimulation (Competent), and (4) Individualized Consideration (Democratic).Overall, it can be concluded that the success of the principal’s leadership is supported by strong cooperation and solidarity among school members, harmonious communication, support from the school committee and community, as well as the principal’s good professional competence.